Pengembangan Bakat dan Minat Peserta Didik melalui Kegiatan Ekstrakurikuler Bahasa Jepang di SMP IT Cendekia Purwakarta - Endang Laelasari; Sri Mulyeni (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the role of Japanese language extracurricular activities in developing students' talents and interests in SMP IT Cendekia Purwakarta. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that Japanese extracurricular activities contribute positively to the development of students' potential, both in academic and non-academic aspects. Students who have a talent for language can hone their skills through conversational activities, writing Japanese letters, and taking part in competitions, while their interest grows due to an interest in Japanese popular culture. In addition, this activity also supports the formation of positive characters such as confidence, discipline, cooperation, and the courage to appear in public. Despite the obstacles in the form of time constraints, difficulties in learning Japanese letters, and lack of facilities, the coaching teachers were able to overcome them with creative learning methods. Thus, Japanese language extracurricular activities have proven to be an effective means of developing students' talents, interests, and personalities, while supporting the school's vision in producing a globally competitive generation.